Fiber reinforced thermoplastics compounds for electromagnetic interference shielding applications - Martins, Luís C. (2022)
Market demands for lightweight and lower cost products drive manufacturers to improve current product portfolios. In the case of electronic devices, the most significant weight originates from the enclosure, traditionally in steel or aluminum, that ensures excellent mechanical and electromagnetic shielding performance. The use of thermoplastics filled with electrically conductive fibers, such as carbon or stainless steel, was investigated as a lightweight and cost-effective alternative to steel sheet for creating electromagnetic interference (EMI) shielding enclosures for electronic devices. This paper presents an EMI shielding analysis workflow for the development of plastic enclosures for an electronic device. The workflow starts by measuring the fiber-reinforced thermoplastic compounds shielding effectiveness (SE) with an experimental method in the 30 MHz–3 GHz frequency band. This analysis helps to filter a vast list of materials with a wide range of shielding performance, 20–100 dB, and allows to obtain empirical data for the second phase of the workflow, computer simulations. Simulations with experimentally adjusted material properties were used to validate the design concept of an enclosure in its early development phase. Results from this study showed that the selected material has better EMI SE performance than a steel sheet venting grid.